Spatial variation of above-ground carbon storage in temperate coastal wetlands. (15th October 2018) - Owers, Christopher J.; Rogers, Kerrylee; Woodroffe, Colin D.
Abstract: Carbon mitigation services provided by coastal wetlands are not spatially homogeneous. The scale of assessment at which above-ground biomass is measured will directly influence carbon storage estimates. Greater confidence in estimates is obtained with approaches that describe more variation. There is a need to improve accuracy while optimising assessment effort efficiency. Accurate quantification of carbon storage is dependent upon accurate assessment of biomass, carbon content and the extent of vegetation for which carbon storage is being assessed. This study demonstrates that vegetation structure influences above-ground biomass of mangrove and saltmarsh, resulting in considerable variability in biomass estimates and associated carbon storage of temperate coastal wetlands in southeast Australia. For mangrove, variability in above-ground biomass (Mg ha −1 ± SE) was best described by measuring height, stem diameter, crown area and vegetation density, whereby tall mangrove (3–8 m in height; 71.50 ± 12.53 Mg ha −1 ) had higher biomass than both shrub (1.3–3 m in height; 53.06 ± 6.94 Mg ha −1 ) and dwarf mangrove (<1.3 m in height; 10.68 ± 1.77 Mg ha −1 ). Saltmarsh above-ground biomass was best described by height, species and vegetation density, which demonstrated significant differences between rush saltmarsh (15.97 ± 2.35 Mg ha −1 ) and herbs, grasses and sedges saltmarsh (7.51 ± 0.91 Mg ha −1 ). The effect of this variation was compounded by carbon content (% C), which varied markedly between vegetation structural form and species (30.9–49.8% C). Maintaining accuracy when assessing carbon storage requires mapping units that correspond to the scale of biomass assessments. Results from this study suggest that recognition of variation in biomass and carbon content of mangrove and saltmarsh vegetation structure will enhance the accuracy of estimates of carbon storage, and provide the confidence necessary for carbon storage inventories. Graphical abstract: Image 1 Highlights: Carbon storage services provided by coastal wetlands are not spatially homogeneous. Mangrove and saltmarsh vegetation structure influences carbon storage. Biomass estimates are optimised when assessed at the structural scale.